Lossless statistical data service over Asynchronous Transfer Mode - van Luinen, Steven M. (Curtin University, 1999)
Asynchronous Transfer Mode (ATM) can provide deterministic channels as required for real time signals, as well as statistical multiplexing. For this reason, ATM has been chosen as the underlying technology for providing a Broadband Integrated Services Digital Network (B-ISDN). Two main classes of services are expected to be supported over a B-ISDN. These classes are real-time services and data services. Data services include computer communications (Local Area Network (LAN) interconnections) and general non-real time traffic, such as file transfer and small transactions.The provision of data services over ATM are better served with statistical multiplexing, provided that the service is loss-free. For multiplexing to be loss-free and still statistical, while the maximum service rate is fixed, the multiplexer tributaries must be controlled in flow, to assure no overflow of the multiplexing buffer. Provision of a service over ATM is accomplished by an ATM layer. Transfer Capability (ATC).This thesis investigates and reports on the operating characteristics of an ATM layer Transfer Capability proposed to the International Telecommunications Union (ITU), and called Controlled Cell Transfer (CCT). CCT uses credit window based flow control on links and a quota based control in switches, and will give loss free statistical multiplexing for data. Other ITU defined ATCs are examined in regard to data service provision and compared with CCT. It is found that only CCT can provide a fast and at the same time efficient data service.The thesis also examines the impact that support of the CCT capability would have on an ATM switch, through determination of required functionality, and mapping of the required functions into a switch design. Finally, an architecture and implementation of an ATM switch is described that would support the CCT as well as the Deterministic Bit Rate (DBR) transfer capability, and would provide efficient data and real-time services.